1996
DOI: 10.1073/pnas.93.21.11693
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear LIM interactor, a rhombotin and LIM homeodomain interacting protein, is expressed early in neuronal development.

Abstract: Genetic studies have demonstrated an essential role for nuclear LIM domain-containing proteins in embryonic development. Disruption of the rhombotin 2 (Rbtn2) gene in mice resulted in embryonic lethality at day 10.5 due to a lack of erythropoeisis (7). Misexpression of Rbtn2 and the related Rbtnl in T cells due to T-cell translocation events leads to T-cell acute lymphoblastic leukemia in children (8-10) or to a leukemia with similar properties in transgenic mice (11-13). The leukemias apparently result from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
197
3
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(216 citation statements)
references
References 33 publications
(35 reference statements)
14
197
3
2
Order By: Relevance
“…The LIM domain of LDBs contributes to the binding of transcription factors, including LIM-homeodomain, zinc-finger and basic helixloop -helix (bHLH) proteins (Agulnick et al, 1996;Jurata et al, 1996;Bach et al, 1997;Morcillo et al, 1997). Formation of protein complexes synergistically activates the expression of target genes Milán et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LIM domain of LDBs contributes to the binding of transcription factors, including LIM-homeodomain, zinc-finger and basic helixloop -helix (bHLH) proteins (Agulnick et al, 1996;Jurata et al, 1996;Bach et al, 1997;Morcillo et al, 1997). Formation of protein complexes synergistically activates the expression of target genes Milán et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The LMO4 gene is widely distributed in embryonic tissues (Kenny et al, 1998;Sugihara et al, 1998), and involved in negative regulation of breast carcinoma cell differentiation (Visvader et al, 2001). LMO4 binds with a high affinity to the LIM domain-binding proteins, LDB1 (CLIM2, NLI1) and LDB2 (CLIM1) (Agulnick et al, 1996;Jurata et al, 1996;Sugihara et al, 1998). LDB proteins bind to transcription factors directly or indirectly mediated through LMO proteins, and then bridge a unique bipartite DNA sequence separated by about one helix turn from each other (Agulnick et al, 1996;Jurata et al, 1996;Wadman et al, 1997;Rabbitts, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the identity of the 46 Kd protein has not been determined because it is obscured by the similarity in its molecular weight of TAL1, which also binds LMO1 (Valge-Archer et al, 1994). A candidate for the 46 Kd protein is the recently identi®ed LIM-binding protein LDB1 or NLI (Agulnick et al, 1996;Jurata et al, 1996) (herein called LDB1). This protein has been shown to interact in vitro with LMO1 and LMO2 (Agulnick et al, 1996;Jurata et al, 1996) and in vivo LMO2 has been found in complexes with LDB1 in erythroid cells (Wadman et al, 1997) and in T cells from Lmo2-transgenic mice (Grutz et al, 1998).…”
mentioning
confidence: 99%
“…A candidate for the 46 Kd protein is the recently identi®ed LIM-binding protein LDB1 or NLI (Agulnick et al, 1996;Jurata et al, 1996) (herein called LDB1). This protein has been shown to interact in vitro with LMO1 and LMO2 (Agulnick et al, 1996;Jurata et al, 1996) and in vivo LMO2 has been found in complexes with LDB1 in erythroid cells (Wadman et al, 1997) and in T cells from Lmo2-transgenic mice (Grutz et al, 1998). We have assessed the interaction of LMO1 and LDB1 in the human T cell acute leukaemia cell line RPMI8402 (which has been t(11;14)(p15;q11)) using a two-step immunoprecipitation protocol described previously (Valge-Archer et al, 1994).…”
mentioning
confidence: 99%